INFORMATION STRUCTURE OF SOCIETY AS A BASIS FOR SYSTEMS FORMATION OF SOCIAL ACTION - A. S. Krul (Дискурс, 2017)
The article presents a modeling example of information and communication structure of the society: main methodological problems of definition of the term are considered, possibilities of studying the information structure of social formations are described. Based on T. Parsons the systems model of social action by and N. Luhmann theory of communicative systems the article describes modeling possibilities of the society information structure. The information structure of some social formations is described.